2019
DOI: 10.1121/2.0001275
|View full text |Cite
|
Sign up to set email alerts
|

Effects of low-frequency noise and temperature on copepod and amphipod performance

Abstract: Offshore wind farms (OWF) are bound to increase as a mitigation strategy to reduce the emission of greenhouse gases, it is crucial to address all of their potential impacts on key ecosystem components in detail. Especially, the chronic effect of noise created during OWF turbine operations (duration 20-25 years) must be understood. As sensitive receptors cover the whole body of crustaceans to detect their surroundings, those low frequency noises may disrupt basic ecological (prey detection and predator avoidanc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
2
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 24 publications
0
6
2
Order By: Relevance
“…Our results are inconsistent with a feeding experiment by Tremblay et al (2019) in which A. tonsa was exposed to a noise egg, a waterproof device that produces low-frequency sound (de Jong et al, 2017). Nevertheless, they found a physiological response correlated with oxidative stress (Tremblay et al, 2019).…”
Section: Mechanisms Of How Underwater Noise Could Affect Capture Ratescontrasting
confidence: 99%
See 2 more Smart Citations
“…Our results are inconsistent with a feeding experiment by Tremblay et al (2019) in which A. tonsa was exposed to a noise egg, a waterproof device that produces low-frequency sound (de Jong et al, 2017). Nevertheless, they found a physiological response correlated with oxidative stress (Tremblay et al, 2019).…”
Section: Mechanisms Of How Underwater Noise Could Affect Capture Ratescontrasting
confidence: 99%
“…Our results are inconsistent with a feeding experiment by Tremblay et al (2019) in which A. tonsa was exposed to a noise egg, a waterproof device that produces low-frequency sound (de Jong et al, 2017). Nevertheless, they found a physiological response correlated with oxidative stress (Tremblay et al, 2019). Hydromechanical disturbances from different prey types are sensed by mechanoreceptive setae on the first antenna of calanoid copepods (Yen et al, 1992;Goncalves and Kiørboe, 2015), such as Acartia sp.…”
Section: Mechanisms Of How Underwater Noise Could Affect Capture Ratescontrasting
confidence: 99%
See 1 more Smart Citation
“…They also suggest a modification of gene expressionbut they did not know the effects of these genes on organisms. A chronic noise exposition of copepods, done by Tremblay et al (2019), also leads to physiological impacts with an alteration of ROS (Reactive Oxygen Species) activities. Therefore, these few studies showed that marine zooplankton can perceive and respond to anthropogenic noises, but their responses remain poorly investigated.…”
Section: Noise Affects Marine Zooplanktonmentioning
confidence: 99%
“…For short-and long-term experiments, we could measure the various parameters as the ROS, the organisms' composition, and the gene expression, providing information regarding the basis of the chain reaction (Dahms et al, 2016). For instance, Lee et al (2019) used various ROS (Glutathione, GST, Glutathione Reductase, GR, Glutathione Peroxidase, GPx, Superoxyde Dismutase, SOD) to determine how ocean acidification affected T. japonicus, and Tremblay et al (2019) observed similar effects for a chronic noise exposition of the copepods Acartia tonsa. Won et al (2014) measured concentration of a copepods' fatty acid due to UV exposition, whereas Prosnier et al (2022a) measured the quantity of carbohydrates, lipids and protein of D. magna infected by a virus.…”
Section: Physiologymentioning
confidence: 99%